Development of Dental Prosthesis Service at Sub-District Health Promoting Hospitals Near Home Under the Huaiyot Model, Trang Province, Thailand - รัตนะ ภัสรา (Journal of Health Science of Thailand, 2022)
The purpose of this study was to develop dental prosthesis service at sub-district health promoting hospitals which would be beneficial for the increase in accessibility and the reduction of the long waiting time for the patients. It was conducted as an action research at Huaiyot Hospital in Trang Province during the years 2015-2019. The process began from a situation review and a study of the performance report, followed by the expansion of dental prosthesis service to participating sub-district health promoting hospitals through the procurement and distribution of dental clinical tools and materials to the sub-district hospitals, rotation of dentists and dental assistants to the sub-district hospitals, development of dental lab skills for dental assistants, and appointment of patients to receive dental prothesis service at local sub-districe hospitals. The results of the study revealed that the Huaiyot Model had gradually extended to cover ten sub-district health promoting hospitals; and the number of patients receiving the dental service in Huaiyot had increased. The patients were able to access the service at a health facility close to their home; and the waiting time reduced from initial 8 months to three months by the end of 2019. As a result, the number of patients receiving dental prosthesis service in Huaiyot became the highest compared to the rest of public hospitals in the province.